Xanthatin induces apoptosis through ROS-mediated c-FLIP inhibition in human retinoblastoma cells - Gao, Xue; Li, Yixiao; Xu, Haoran; Ni, Shouxiang; Pan, Hong; Ma, Chunli; Zhao, Xiaofei; Zhang, Han (Frontiers in Medicine, 2025)
Retinoblastoma is widely considered the most frequent primary intraocular malignancy during childhood. Xanthatin has been reported to selectively inhibit the proliferation of RB cells, but the underlying mechanism remains uncertain. In this study, human RB cells were treated with different doses of xanthatin, and then cell survival, cell apoptosis, and protein expression were assessed using CCK8 assays, flow cytometry, and western blotting to investigate the possible mechanism of xanthatin in RB cells. A human RB xenograft model was established to demonstrate the effect of xanthatin in vivo. Our study shows that xanthatin inhibited cell survival and induced apoptosis in human RB cells. Moreover, xanthatin induced the downregulation of CASP8 and FADD-like apoptosis regulating protein (c-FLIP) and increased the cleavage of caspase-8, caspase-9, caspase-3, and PARP. c-FLIP overexpression impaired xanthatin-induced apoptosis. Furthermore, NAC, which can reduce xanthatin-triggered Reactive oxygen species (ROS), alleviated xanthin-induced apoptosis and c-FLIP downregulation. In vivo, analysis confirmed that xanthatin was an efficacious drug against xenograft tumors. Xanthatin induced apoptosis of the human RB cells both in vivo and in vitro through ROS-mediated c-FLIP inhibition. Our research provides important mechanistic insight into potential cancer treatments with ROS/c-FLIP axis in xanthatin-induced apoptosis and makes them candidates for developing new directed therapies.